2018
DOI: 10.5114/hm.2019.79041
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of injuries and its association with the characteristics of training in American football players in Brazil

Abstract: American football is a high-impact collision sport, which may lead to high injury rates in the players. thus, knowing the aetiology and incidence of injuries may be useful not only for the treatment, but especially to help sports professionals to develop strategies or mechanisms of prevention while aiming to maintain the physical integrity of the athletes. Purpose. the aim of the study was to verify the prevalence of injury among American football players from the Santa Catarina state of Brazil. Methods. the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Our findings support the results presented by Wilborn et al (2004), in which authors also found an increase in lean mass and a decrease in body fat in both ZMA and placebo groups, non presenting differences among them as well. The characteristics of our sample are in line with the ones presented in studies that evaluated Brazilian amateur football teams [12][13][14] . Concerning hormone levels, there was increase in both groups, compared with themselves.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings support the results presented by Wilborn et al (2004), in which authors also found an increase in lean mass and a decrease in body fat in both ZMA and placebo groups, non presenting differences among them as well. The characteristics of our sample are in line with the ones presented in studies that evaluated Brazilian amateur football teams [12][13][14] . Concerning hormone levels, there was increase in both groups, compared with themselves.…”
Section: Discussionsupporting
confidence: 76%
“…this suggests a low level of awareness of physiotherapy and athletic trainers' role in the management of football injuries. Previous studies have also shown that much training and participation can as well lead to high prevalence of sporting injuries [22][23]. thus, not only the medical team but also the coaches and trainers should be responsible for injury prevention and rehabilitation.…”
Section: Pattern Of Football Injurymentioning
confidence: 99%